2019
DOI: 10.1037/tra0000475
|View full text |Cite
|
Sign up to set email alerts
|

Meaning in life moderates the association between morally injurious experiences and suicide ideation among U.S. combat veterans: Results from the National Health and Resilience in Veterans Study.

Abstract: Objective: Effectively responding to suicide risk among veterans involves further developing understanding of reactions to combat experiences, including life-threatening events, traumatic losses, and morally injurious experiences. An important determinant of whether stressors lead to poor mental health outcomes is the perception of meaning. The current study aimed to determine whether global meaning (i.e., general beliefs, goals, and sense of purpose in life) moderates the relationship between morally injuriou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 39 publications
2
16
0
Order By: Relevance
“…Our results are consistent with previous studies that have demonstrated that meaning in life moderates the association between morally injurious events and suicidal ideation (Bryan et al, 2013; Corona et al, 2019). More globally, our findings also support research demonstrating that a higher presence of meaning in life is associated with psychological growth after traumatic events (e.g., Calhoun & Tedeschi, 2006; Janoff-Bulman, 2006; Park, 2010).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results are consistent with previous studies that have demonstrated that meaning in life moderates the association between morally injurious events and suicidal ideation (Bryan et al, 2013; Corona et al, 2019). More globally, our findings also support research demonstrating that a higher presence of meaning in life is associated with psychological growth after traumatic events (e.g., Calhoun & Tedeschi, 2006; Janoff-Bulman, 2006; Park, 2010).…”
Section: Discussionsupporting
confidence: 93%
“…Studies have shown that meaning in life moderates the association between morally injurious events and suicidal ideation in service members (e.g., Bryan et al, 2013; Corona et al, 2019). In general, individuals who can make meaning from traumatic events report a higher presence of meaning in life and greater growth and psychological well-being (Calhoun & Tedeschi, 2006; Janoff-Bulman, 2006; Park, 2010).…”
Section: Moral Injury and Suicidementioning
confidence: 99%
“…Transgressions, acts, or behaviours undertaken in military service can incite deep feelings of distrust, anger, shame, and guilt (Litz et al 2009;Tangney et al 2007;Vargas et al 2013). The transgressive act or behaviour may be intrapersonally evaluated as a threat to the integrity of one's moral schema, or a moral disorientation (Molendijk 2018) resulting in negative psychological and emotional consequences that can heighten the risk of suicide in veterans (Bryan et al 2014;Corona et al 2019;Kelley et al 2019;Koenig et al 2019b).…”
mentioning
confidence: 99%
“…Meaning in life in the context of distress may be a protective factor in preventing worsening mental health among veterans. Higher meaning in life is associated with lower suicidal ideation after morally injurious events (Corona et al, 2019) and is also associated with improvement in depression and hopelessness among previously depressed veterans (Braden et al, 2017). Curiously, we saw no differences in meaning in life across demographic characteristics.…”
Section: Discussionmentioning
confidence: 99%